Triphenyl phosphate exacerbates lung cancer metastasis by activating NF-κB signaling pathway - Shuangshuang Shi; Wenhui Zong; Shengnan Gao; Wenqiu Ding; Yuan Dai; Songtao Liu; Nan Li; Weiping Xie; Hui Kong; Qun Zhang (Environmental Pollution, 2026)

Manipulating the organic-salt selectivity of N-2-hydroxyethylpiperazine based poly-ester-amide (PEA) membranes for antibiotic-NaCl separation - Qinghua Guo; Tao Shi; Lu Dai; Zhiguo Yan; Qun Chen; Man Xu; Yanbo Li (Desalination, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Transcriptomic reprogramming underlies melatonin-mediated enhancement of cadmium tolerance and lateral root growth in soybean - Rongrong Li; Jinming Kou; Xiaoqiong Liu; Hengrui Dai; Ze Liu; Qun Chen; Tanveer Ahmad Khan; Xinjia Wang; Yanli Chen; Qi Chen; Xiaojun Pu (Journal of Hazardous Materials, 2026)

Decoupling of Fe isotope and Fe3+/ΣFe in arc igneous rocks: Implications for crustal metasomatism and its contribution to mantle redox - Li-Tao Ma; Li-Qun Dai; Zi-Wei Yao; Zi-Fu Zhao; Ye-Dan Hu; Zhen-Wu Chen; Guo-Chao Sun (Geochimica et Cosmochimica Acta, 2026)

Oat β-glucan reshapes gut microbiota to enhance glucose homeostasis via coordinated modulation of bile acid conjugation and succinate-dependent intestinal gluconeogenesis - Yantong Meng; Siqi Li; Keyi Zhou; Zhuoma Suonan; Zijian Dai; Qun Shen; Yong Xue (Food Chemistry, 2026)

Molybdenum isotopes in metamorphic and magmatic rocks may record substantial fluid activity in continental subduction zones - Wei Fang; Li-Qun Dai; Ren-Xu Chen; Zi-Fu Zhao (Chemical Geology, 2026)

Effect of structural characteristics of highland barley β-glucan by various thermal processing methods on intestinal microbial community and fermentative products - Rong Li; Ji Gao; Yiyun Zhang; Zijian Dai; Siqi Li; Tong Wu; Jiaqian Cao; Kefan Wei; Chao Wang; Qun Shen; Yong Xue (Food Bioscience, 2026)

Intrinsic capacity across the adult lifespan in China: baseline analysis from the nationwide longitudinal PENG ZU cohort - Ju Cui; Yujia Gu; Jing Pang; Huafang Gao; Li-Qun Zhang; Xiaolan Wu; Junwu Dang; Juan Li; Xinyi Zhu; Senlin Luo; Zhao Wang; Fuyi Tu; et al. (GeroScience, 2026)

Micro-granular sludge driven by powder carrier in membrane bioreactor: highly-efficient N & P removal and membrane fouling alleviation - Boran Wu; Junqian Zhong; Hao Chang; Dong Li; Chengxian Wang; Hongbo Han; Qun Gu; Yan Zhong; Xiaohu Dai; Xiaoli Chai (Water Research, 2026)

The Reorganization of Cerebellar Functional Network Topology in Post-stroke Aphasia: A Resting-State fMRI Study - Liting Chen; Zhenye Luo; Wenfeng Mai; Xiaoling Wu; Xiaole Fan; Lifeng Li; Yongqiang Shu; Xiaoyun Chen; Qun Fang; Hong Wang; Yanhong Dai; Shuixing Zhang (Molecular Neurobiology, 2026)

Water-resistant and antibacterial food packaging films prepared from bamboo shoot shell cellulose nanofibers and cinnamaldehyde/chitosan emulsion - Lianying Dai; Qun Liu; Meng Li; Xialing Wu; Wenhui Zheng; Wuyin Weng; Yucang Zhang (Food Hydrocolloids, 2025)

Aerodynamically assisted biomimetic multifunctional device for simultaneous fog water harvesting and triboelectric energy generation - Changzheng Li; Fuyuan He; Ruishi Gan; Ziyuan Liang; Jingying Dai; Mengzhen Liao; Tao Rui; Zhi Qun Tian (Chemical Engineering Journal, 2025)

Chalcophile elements in post-subduction magmas and implications for metal recycling in oceanic and continental subduction - Xiang Wang; Zaicong Wang; Li-Qun Dai; Wen Zhang; Xiaodong Deng; Xi Zhang; Stephen Foley; Charles H. Langmuir; Wei Fang; Lang Wang; Tao He; Aiqing Ren; et al. (Geochimica et Cosmochimica Acta, 2025)

Myxomycetes in urban green space in subtropical China: Spatiotemporal patterns override forest type effects - Wen-Long Song; Di Lin; Min-Li Cai; Xia Chen; Qun Dai; Shuang-Lin Chen (Fungal Biology, 2025)

DPP-IV inhibitory peptides from highland barley via machine learning and multi-scale validation - Xin Bao; Yiyun Zhang; Liyang Wang; Zijian Dai; Rong Li; Kefan Wei; Jiaqian Cao; Qingyu Zhao; Qun Shen; Yong Xue (Food Chemistry, 2025)

Self-reconstructed Cu2O/Co3O4@NC heterostructured catalyst for efficient tandem electrocatalytic conversion of nitrate to ammonia - Lin Zhu Dai; Guo Yu Yong; Wan Ni Gan; Ting Li; Zhi Cheng Chen; Lun Yao Pan; Hong Qun Luo; Nian Bing Li (Chemical Engineering Journal, 2025)

Molybdenum isotopes record slab inputs to the mantle source of late Triassic Arc Lavas, Northeast China - Zhigang Wang; Hui-Dong Zhang; Li-Qun Dai; Zi-Fu Zhao; Wei Fang (Chemical Geology, 2025)

Diffusion-driven zircon Zr isotopic fractionation during ultramafic–mafic magmatic differentiation - Li-Tao Ma; Li-Qun Dai; Shao-Bing Zhang; Ren-Xu Chen; Qiong-Xia Xia; Zi-Fu Zhao (Geochimica et Cosmochimica Acta, 2025)

Key role of recycled terrigenous sediments in generating continental arc magmatism in the West Qinling orogen, China - Li-Tao Ma; Li-Qun Dai; Hao Liang; Ye-Dan Hu; Qing-Cheng Yang; Zi-Fu Zhao; Guo-Chao Sun (Chemical Geology, 2025)

COP1 Overexpression Attenuates Nociceptive Behaviors and Neuroinflammation in Cancer-Induced Bone Pain by Suppressing c/EBPβ - Dan-Yang Li; Lin Liu; Shao-Jie Gao; Dai-Qiang Liu; Long-Qing Zhang; Jia-Yi Wu; Fan-He Song; Xin-Yi Dai; Ya-Qun Zhou; Wei Mei (Journal of Neuroimmune Pharmacology, 2025)

Machine learning discovery of novel antihypertensive peptides from highland barley protein inhibiting angiotensin I-converting enzyme (ACE) - Xin Bao; Yiyun Zhang; Liyang Wang; Zijian Dai; Yiqing Zhu; Mengyao Huo; Rong Li; Yichen Hu; Qun Shen; Yong Xue (Food Research International, 2025)

Origin of the coeval Nb-enriched and arc mafic igneous rocks: Implications for Paleozoic tectonic evolution of the Southwestern Tianshan - Li-Tao Ma; Li-Qun Dai; Ye-Dan Hu; Zi-Fu Zhao (Chemical Geology, 2025)

Salinity affects C/N ratio through differential responses of carbon and nitrogen metabolism in mangrove Avicennia marina leaves revealed by combined analysis of transcriptome and metabolome - Jing Li; Ling-Yu Song; Ze-Jun Guo; Chao-Qun Xu; Lu-Dan Zhang; Ji-Cheng Wang; Han-Chen Tang; Ming-Jin Dai; Xue-Yi Zhu; Hai-Lei Zheng (Plant and Soil, 2025)

Biocontrol potential of Streptomyces sp. N2 against green and blue mold disease in postharvest navel orange and the action mechanism - Shuaiying Peng; Chao Duan; Qun Liu; Qian Wang; Yuqi Dai; Liwen Hao; Kuntai Li (Food Microbiology, 2025)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Post-collisional reworking of juvenile mafic lower crust for the petrogenesis of late Triassic adakitic rocks in the East Kunlun Orogen - Gang Wen; Guo-Chao Sun; Zi-Fu Zhao; Li-Qun Dai; Yao Zhou (Lithos, 2024)

Remnants and fragments of the subducted paleo-Pacific plate: Constraints from geochemistry and geophysics - Xisheng Xu; Zhouchuan Huang; Dingsheng Jiang; Gang Zeng; Li-Qun Dai (Science China Earth Sciences, 2024)

Secular mantle wedge evolution due to variable slab fluid metasomatism: Evidence from Permian-Triassic mafic igneous rocks in the Paleo-Tethys tectonic regime - Ye-Dan Hu; Li-Qun Dai; Li-Tao Ma; Zi-Fu Zhao (Chemical Geology, 2024)

Sodic adakitic granites in the East Kunlun Orogen, China: Partial melting of ultrahigh-pressure metamorphic terranes during continental collision - Lei Qin; Guo-Chao Sun; Peng Gao; Zi-Fu Zhao; Li-Qun Dai; Gang Wen; You-Shan Xia; Yao Zhou (Chemical Geology, 2024)

Molybdenum isotopic evidence for the initiation of a big mantle wedge beneath eastern Asia - Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Qi Chen; Jun Yan; Dayu Zhang; Ding-Sheng Jiang (Chemical Geology, 2024)

Triphenylamine promoted geometric structure adjusting of the novel macrocyclic structure D-π-A conjugated microporous polymers for photocatalytic hydrogen evolution - Fengrui Li; Xiao Dai; Linfeng Zhang; Huadong Wu; Jianding Li; Jia Guo; Qun Yi (Fuel, 2024)

In-situ trace element and Sr isotope in mantle xenoliths from the West Qinling orogen: Evidence for carbonate metasomatism - Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Guo-Chao Sun (Lithos, 2024)

In situ mass spectrometry imaging reveals pesticide residues and key metabolic pathways throughout the entire cowpea growth process - Shufan Jiang; Jingling Lin; Rui Zhang; Qiong Wu; Hongxing Li; Qun Zhang; Mingyue Wang; Longjun Dai; Defang Xie; Yue Zhang; Xinzhong Zhang; Bingjun Han (Journal of Hazardous Materials, 2024)

Syn- and post-collisional mafic igneous rocks from the East Kunlun Orogenic Belt: Implications for recycling of subducting continental crust during the Silurian-Devonian - Li-Tao Ma; Guo-Chao Sun; Li-Qun Dai; Zi-Fu Zhao; Ye-Dan Hu; Qing-Cheng Yang; Lei Qin; Bing Gong (Lithos, 2024)

Mo-Mg isotopes trace the role of serpentinite in generating arc magmatism - Qing-Chen Yang; Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Guo-Chao Sun; Bing Gong (Chemical Geology, 2024)

Draft Genome Sequence of Candida saopaulonensis from a Very Premature Infant with Sepsis - Ya-Ting Ning; Rong-Chen Dai; Zheng-Yu Luo; Meng Xiao; Yingchun Xu; Qun Yan; Li Zhang (Mycopathologia, 2024)
The rare fungus Candida saopaulonensis has never been reported to be associated with human infection. We report the draft genome sequence of the first clinical isolate of C. saopaulonensis, which was isolated from a very premature infant with sepsis. This is the first genome assembly reaching the near-complete chromosomal level with structural annotation for this species, opening up avenues for exploring evolutionary patterns and genetic mechanisms of pathogenesis.

Microbial mediation of soil carbon loss at the potential climax of alpine grassland under warming - Zhengxiong Liang; Xue Guo; Suo Liu; Yifan Su; Yufei Zeng; Changyi Xie; Qun Gao; Jiesi Lei; Baochan Li; Mei Wang; Tianjiao Dai; Liyuan Ma; et al. (Soil Biology and Biochemistry, 2024)

Molybdenum isotopic heterogeneity for intraplate basalts and its origin - Wei Fang; Li-Qun Dai; Zi-Fu Zhao (Chemical Geology, 2023)

Mo isotopes record recycling of anoxic sediment in a Paleo-oceanic subduction zone - Xiang Fu; Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Bing Gong; Yong-Fei Zheng (Chemical Geology, 2023)

High efficient alkaline hydrogen evolution catalyzed by W2COx-Ru composite system containing bridged oxygen - Yu Dai; Hong Chuan Fu; Xiao Hui Chen; Qing Zhang; Ting Li; Nian Bing Li; Hong Qun Luo (Chemical Engineering Journal, 2023)

Trace elements and Li isotopes distinguish between liquid and solid phases contributing to mafic arc magmas - Li-Tao Ma; Li-Qun Dai; Yong-Fei Zheng; Zi-Fu Zhao; Bing Gong; Yilin Xiao; Fengtai Tong (Lithos, 2023)

Inventory of cadmium-transporter genes in the root of mangrove plant Avicennia marina under cadmium stress - Lu-Dan Zhang; Ling-Yu Song; Ming-Jin Dai; Jin-Yu Liu; Jing Li; Chao-Qun Xu; Ze-Jun Guo; Shi-Wei Song; Jing-Wen Liu; Xue-Yi Zhu; Hai-Lei Zheng (Journal of Hazardous Materials, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Targeted delivery of nutraceuticals derived from food for the treatment of obesity and its related complications - Zijian Dai; Yiyun Zhang; Yantong Meng; Siqi Li; Zhuoma Suonan; Yuge Sun; Junfu Ji; Qun Shen; Hao Zheng; Yong Xue (Food Chemistry, 2023)

Molybdenum isotopes record recycling of subducting sediment in active continental margin, Northeast China - Wei Fang; Li-Qun Dai; Xiang Fu; Zi-Fu Zhao; Bing Gong; Yong-Fei Zheng (Chemical Geology, 2023)

Temporal geochemical variation in early Paleozoic mafic rocks from the Qinling orogen: Implications for the evolution of slab fluids during oceanic subduction - Hai-Yang Yan; Guo-Chao Sun; Zi-Fu Zhao; Li-Qun Dai; Fei Zheng (Chemical Geology, 2023)

Deep learning drives efficient discovery of novel antihypertensive peptides from soybean protein isolate - Yiyun Zhang; Zijian Dai; Xinjie Zhao; Changyu Chen; Siqi Li; Yantong Meng; Zhuoma Suonan; Yuge Sun; Qun Shen; Liyang Wang; Yong Xue (Food Chemistry, 2023)

Distinct contribution of aqueous solutions and hydrous melts to the mantle sources: Geochemical evidence from Late Paleozoic igneous rocks in Southwestern Tianshan, Western China - Li-Tao Ma; Li-Qun Dai; Zi-Fu Zhao; Fang Huang; Bing Gong (Lithos, 2023)

The heterogeneous orogenic lithospheric mantle: whole rock and mineral geochemical evidence from early Paleozoic mafic intrusives in the Qilian orogen, China - Qi Chen; Li-Qun Dai; Zi-Fu Zhao; Yong-Fei Zheng; Yao Zhou (Contributions to Mineralogy and Petrology, 2022)

The Arabidopsis KH-domain protein FLOWERING LOCUS Y delays flowering by upregulating FLOWERING LOCUS C family members - Guang-Yi Dai; Ding-Kang Chen; Yun-Peng Sun; Wei-Yi Liang; Yu Liu; Li-Qun Huang; Yong-Kang Li; Jia-Fan He; Nan Yao (Plant Cell Reports, 2020)

The effect of blastomere loss during frozen embryo transfer on the transcriptome of offspring’s umbilical cord blood - Yan-Ting Wu; Ze-Han Dong; Cheng Li; Dai-Zhan Zhou; Jun-Yu Zhang; Yan Wu; Jing-Jing Xu; Yu Wang; Xiao-Qun Ye; Jian-Zhong Sheng; Li Wang; He-Feng Huang (Molecular Biology Reports, 2020)

Comparative Pharmacokinetics of Nimodipine in Rat Plasma and Tissues Following Intraocular, Intragastric, and Intravenous Administration - Fang Li; Qingsong Fei; Dan Mao; Qiaoyun Si; Manman Dai; Qun Ma; Huimin Zhang; Luyu Bai; Ning He (AAPS PharmSciTech, 2020)

The P450 oxidoreductase (POR) rs2868177 and cytochrome P450 (CYP) 2B6*6 polymorphisms contribute to the interindividual variability in human CYP2B6 activity - Li-chen Gao; Fang-qun Liu; Li Yang; Lin Cheng; Hai-ying Dai; Ran Tao; Shi-Peng Cao; Di Wang; Jie Tang (European Journal of Clinical Pharmacology, 2016)

Rutaecarpine attenuates hypoxia-induced right ventricular remodeling in rats - Wen-Qun Li; Xiao-Hui Li; Jie Du; Wang Zhang; Dai Li; Xiao-Ming Xiong; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Nonylphenol biodegradation, functional gene abundance and bacterial community in bioaugmented sediment: effect of external carbon source - Zhao Wang; Yu Dai; Qun Zhao; Ningning Li; Qiheng Zhou; Shuguang Xie (Environmental Science and Pollution Research, 2015)

Characterization of mineralogy and surface zeta potential of atmospheric dust fall in northwest China - Fa-Qin Dong; Wu Chen; Qun-Wei Dai; Yue-Quan Deng; Ping He; Xiao-Chun He; Jun Tang; Li-Zhu Liu; Hua He (Mineralogy and Petrology, 2015)

Bioremediation using Novosphingobium strain DY4 for 2,4-dichlorophenoxyacetic acid-contaminated soil and impact on microbial community structure - Yu Dai; Ningning Li; Qun Zhao; Shuguang Xie (Biodegradation, 2015)

Nicotine-induced upregulation of VCAM-1, MMP-2, and MMP-9 through the α7-nAChR-JNK pathway in RAW264.7 and MOVAS cells - Zong-Zhuang Li; Zhen-Zhen Guo; Zhi Zhang; Qun-An Cao; Ya-Juan Zhu; Hua-Li Yao; Li-Li Wu; Qiu-Yan Dai (Molecular and Cellular Biochemistry, 2015)

Lowered Nudix type 5 (NUDT5) expression leads to cell cycle retardation in HeLa cells - Li-Qun Zhang; Da-Peng Dai; Wei Gan; Yasumitsu Takagi; Hiroshi Hayakawa; Mutsuo Sekiguchi; Jian-Ping Cai (Molecular and Cellular Biochemistry, 2012)